Simple and rapid peptide nanoprobe biosensor for the detection of: Legionellaceae - Alhogail, Sahar; Chinnappan, Raja; Alrifai, Majeda; Suaifan, Ghadeer A. R. Y.; Bikker, Floris J.; Kaman, Wendy E.; Weber, Karina; Cialla-May, Dana; Popp, Jürgen; Alfageeh, Mohamed B.; Al-Kattan, K.; Zourob, Mohammed M. (Analyst, 2021)
This study demonstrates the development of a sensitive, specific, and quantitative peptide-based nanoprobe prototype assay for the detection of Legionellaceae in a simple way and in a short time. In this work, proteases present in the culture supernatants of Legionella spp. were used as a biomarker. Fluorogenic peptide substrates, specific to Legionella strains culture supernatant proteases, were identified. Peptidases produced a significant increase in the fluorescence intensity following the cleavage of the dipeptide fluorogenic substrates. The specific substrates were identified and coupled with carboxyl-terminated nano-magnetic particles (NMPs). On the other hand, the C-terminal was conjugated with the cysteine residue to covalently integrate with a gold sensing platform via the Au-S linkage. Four different sensors were fabricated from the four specific substrates, which were treated with the protesase of six different species of Legionella. In the presence of specific protease, the peptide sequence is digested and the magnetic nanobeads moved out of the gold surface, resulting in the apparence of gold color. One of the nanoprobes sensitivity detects as low as 60 CFU mL-1 of Legionella anisa, Legionella micdadei, and Fluoribacter dumoffii. The cross-reactivity of the sensors was tested using other closely associated bacterial species and no significant cross-reactivity of the sensors was found. It is envisaged that this assay could be useful for screening purposes or might be supportive for the fast and easy detection of Legionella protease activity for water monitoring purposes.
CRIS-Team Scopus Importer:2023-04-20